Manual of Fertilizer Processing. - Nielsson (Routledge, 2018)
This Manual of Fertilizer Processing, which is the fifth volume of the Fertilizer Science and Technology series. Francis (Frank) T. Nielsson, the editor of the book, has over 40 years of experience in the fertilizer industry, ranging from ammonia manufacture to the extraction of uranium from phosphoric acid, but he is best known for his work with compound or "mixed" fertilizers-fertilizers that contain two or more of the primary plant nutrients: nitrogen, phosphorus, and potassium. Compound fertilizers also may contain one or more of the ten other elements that are essential to plant growth.
Products Containing Soluble Methyleneureas.
Keywords: Fertilizers -- Handbooks, manuals, etc.; elektronické knihy; electronic books